Synthesis and Characterization of SiO2/ZnO Nanocomposites from Zinc Waste and Mount Merapi Volcanic Ash - Sunardi Sunardi; Silviana Silviana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Research on the synthesis and characterization of SiO2/ZnO nanocomposites from zinc waste and Mount Merapi volcanic ash has been carried out. The semiconductor used was ZnO using a SiO2 as the host material. The use of SiO2 was due to its high efficiency and abundant raw materials. This is because the eruption of Mount Merapi occurs regularly every four years. Apart from the abundant presence of SiO2, the source of ZnO from lathe workshop waste is also easy to obtain. The research aims to reduce the volume of zinc waste from the lathe and volcanic ash, which was not optimized. Zinc waste and volcanic ash were synthesized into nanocomposites. Then the obtained nanocomposites were characterized to determine their effectiveness in degrading various wastes. The synthesis of SiO2/ZnO nanocomposites was carried out using the sol-gel method as easy and highly effective. The method used is to transform zinc waste into Zn(OH)2. The volcanic ash was extracted with KOH to form potassium silicate (K2SiO3). Zn(OH)2, (K2SiO3) and HCl were reacted together when sonicated, then calcined at 550°C. The results showed that SiO2/ZnO nanocomposites made from volcanic ash and zinc waste produced composite sizes with a size range of 100-200 nm and a uniform circular shape. FTIR analysis results show that SiO has the peaks at wavenumbers of 993.34 and 1109.07 cm-1, while the ZnO peak is at wavenumbers of 443.63 cm-1. The XRD diffractogram of SiO2/ZnO nanocomposites shows peaks at 2θ of 30.42°, 31.56°, and 44.40°.